Altruism and social learning theory; an analysis of gender differences - Dinkha, Juliet (2012)
Previous research shows that women are more altruist than men in dictator game experiments. Yet, little is known whether women are expected to be more altruist than men. Here we elicit third-parties' beliefs about dictators' donations conditional on knowing the gender of the dictator. Our data provide evidence of three main findings: (i) women are expected to be more altruist than men; (ii) both men and women have correct beliefs about the level of altruism among men; and (iii) both men and women overestimate the level of altruism among women. In doing so, our results uncover a perception gap according to which, although women are more altruist than men, they are expected to be even more altruist than they actually are.